KEPEMIMPINAN DALAM BUDAYA ORGANISASI - BURHANUDIN MUKHAMAD FATURAHMAN (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2018)
Leadership is a major factor in the achievement of the organization goal. However the achievement of goals in an effort to keep observing the behavior of his subordinates where such behaviour form a culture within the organization. The behavior of such subordinates as consideration by the conduct for a decision. Theory X and Y represent the behavior of individual antagonists and cooperative in the organization. By understanding different behavior then it is entirely circumstantial right approach through participatory leadership. This shows that even though the leader has the full authority against the control of the Organization, still could not rule out the role of the subordinate.